Computational Aesthetics - Suzuki, Yasuhiro; Nakagawa, Katsushi; Sugiyama, Takashi; Akiba, Fuminori; Maestri, Eric.; Choi, Insil; Tsuchiya, Shinya; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2019)
The essence of natural computing is aesthetics; for example, in cooking, one of the most common forms of natural computation, the decision to add salt, and how much, is based on the aesthetics of taste. Because touch perception is instinctively related to a sense of beauty, the aesthetics of tactile sense are considered as algorithms by using the Tactile Score, which encodes tactile sensation. This book will appeal not only to researchers of natural computing or aesthetics, but also those working in ergonomic design, haptic-Kansei engineering, philosophy, design and art.
Computational Aesthetics -- The Significance of Natural Computing for Considering Computational Aesthetics of Nature.-Herder on "Sentio, Ergo Sum": Seen from his Remarks on the Color Harpsichord -- A historical perspective on sound art and its relationship to tactile sense -- A Spectro-gestural-morphological Analysis of a Musical-tactile score -- Think of everything with back calculation - Computational aesthetics of hair design.
Keywords: Computational intelligence; Image processing -- Digital techniques; Computer vision; Cognitive psychology; Computational Intelligence; Computer Imaging, Vision, Pattern Recognition and Graphics; Cognitive Psychology